2020
DOI: 10.1007/s42532-020-00058-z
|View full text |Cite
|
Sign up to set email alerts
|

Combining experiential and social learning approaches for crop disease management in a smallholder context: a complex socio-ecological problem

Abstract: Effective management of crop diseases is a key precondition for sustainable crop production and to improve food security globally. However, learning approaches that improve smallholder farmers’ knowledge, perceptions, and practices to deal with crop diseases by fostering social and technical innovations are seldom studied. A study was conducted to examine: (1) how a combination of experiential and social learning approaches influences potato farmers’ knowledge, perceptions, and practices in bacterial wilt and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
(77 reference statements)
3
6
0
Order By: Relevance
“…Participants repeatedly expressed their sense of gratitude and excitement because they learned both about technical aspects of the disease as well as interdependencies and collective action requirements. Our findings aligned with Tafesse et al (2020), who found a need for learning approaches that support the diffusion of both technical disease aspects as well as giving attention to the existence of interdependencies and needs for collective action [37]. Given the feedback that we received from farmers, our method met those characteristics in that it let farmers actively experience their interdependence while also teaching them technical disease information.…”
Section: The Learning Effect Of Playing Togethersupporting
confidence: 86%
“…Participants repeatedly expressed their sense of gratitude and excitement because they learned both about technical aspects of the disease as well as interdependencies and collective action requirements. Our findings aligned with Tafesse et al (2020), who found a need for learning approaches that support the diffusion of both technical disease aspects as well as giving attention to the existence of interdependencies and needs for collective action [37]. Given the feedback that we received from farmers, our method met those characteristics in that it let farmers actively experience their interdependence while also teaching them technical disease information.…”
Section: The Learning Effect Of Playing Togethersupporting
confidence: 86%
“…Participants repeatedly expressed their sense of gratitude and excitement because they learned both about technical aspects of the disease as well as interdependencies and collective action requirements. Our findings align withTafesse et al (2020) who found a need for learning approaches that support the diffusion of both technical disease aspects as well as giving attention to the existence of interdependencies and needs for collective action. Given the feedback that we received from farmers, our method meets those characteristics in that it lets farmers actively experience their interdependence while also teaching them technical disease information.…”
supporting
confidence: 89%
“…This necessitates strengthening of the capacity of seed potato cooperatives to become effectively involved in quality declared seed production through a robust monitoring system. Improving farmers' knowledge and practices through experiential and social learning approaches should be prioritised to foster collective action involving both seed and ware potato growers [57]. Developing quarantine systems could also support efforts to control the disease in the country's smallholder potato production.…”
Section: Detection and Characterisation Of Ralstonia Solanacearum Strainsmentioning
confidence: 99%